Post-Pandemic MSME’s and Sustainable Development in Solo City - Maulidyah Indira Hasmarini; Ali Zainal Abidin; Kenny Pradipta Montoya Putra Pratama (Universitas Negeri Semarang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a pivotal role in Indonesia’s economy, accounting for approximately 60% of the national GDP and employing 97% of the workforce. However, the COVID-19 pandemic severely disrupted MSME sustainability, particularly in Solo, thereby impacting their contribution to the Sustainable Development Goals (SDGs). This study explores the role of MSMEs in advancing the SDGs and identifies the challenges they face. Employing a qualitative case study approach, data were collected through in-depth interviews with 15 purposively selected MSME actors. Thematic analysis revealed that MSMEs contribute significantly to SDG 8 (Decent Work and Economic Growth) by sustaining employment, to SDG 9 (Industry, Innovation, and Infrastructure) through digital adaptation, and to SDG 10 (Reduced Inequalities) by promoting inclusive entrepreneurship. Despite these contributions, MSMEs continue to face obstacles, including declining revenues, restricted access to financing, and supply chain disruptions. The findings underscore the need for targeted policy interventions, including streamlined financial access, capacity-building initiatives, and infrastructure support. Strengthening digital literacy and fostering collaborative business ecosystems are essential strategies to enhance the resilience and long-term sustainability of MSMEs in the post-pandemic recovery phase